2011
DOI: 10.1017/s1461145710001641
|View full text |Cite
|
Sign up to set email alerts
|

Factors modifying drug and placebo responses in randomized trials for bipolar mania

Abstract: Randomized placebo-controlled trials (RCTs) are standard for assessing efficacy and safety of treatments. We pursued preliminary indications that some factors are associated differentially with responses to placebo or drugs in RCTs for bipolar mania. We meta-analysed data from RCTs to assess influences of study-site count, subjects' age, sex distribution, diagnostic subgroups, clinical features, trial-completion rates, and publication year on mean difference (MD) in mania ratings between intake and final asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 56 publications
3
50
0
Order By: Relevance
“…Among the patient characteristics frequently accused of driving the placebo response are sex (with larger placebo responses in women) and (younger) age. Although these factors were shown to be relevant in some trials (Thijs et al, 1990;Freeman and Rickels, 1999;Rheims et al, 2008;Cohen et al, 2010;Yildiz et al, 2011;Agid et al, 2013;Arakawa et al, 2015), a recent review (Weimer et al, 2015a) of 75 systematic reviews and metaanalyses including more than 1500 trials, 150,000 patients, and 40 medical indications revealed that age and sex were not significant predictors of placebo responses in RCT, despite occasional evidence from experimental research (Aslaksen et al, 2007;Weimer et al, 2013b).…”
Section: B Influence Of Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the patient characteristics frequently accused of driving the placebo response are sex (with larger placebo responses in women) and (younger) age. Although these factors were shown to be relevant in some trials (Thijs et al, 1990;Freeman and Rickels, 1999;Rheims et al, 2008;Cohen et al, 2010;Yildiz et al, 2011;Agid et al, 2013;Arakawa et al, 2015), a recent review (Weimer et al, 2015a) of 75 systematic reviews and metaanalyses including more than 1500 trials, 150,000 patients, and 40 medical indications revealed that age and sex were not significant predictors of placebo responses in RCT, despite occasional evidence from experimental research (Aslaksen et al, 2007;Weimer et al, 2013b).…”
Section: B Influence Of Patient Characteristicsmentioning
confidence: 99%
“…Several RCT characteristics that increase placebo response rates have been identified in individual re-and meta-analyses. These include numerous study sites participating in multicenter studies (Bridge et al, 2009;Yildiz et al, 2011;Capurso et al, 2012), longer trial duration (Su et al, 2004;Fulda et al, 2007), and RCTs performed in Europe rather than the United States (Macedo et al, 2006;. These factors have changed during the last decades and might account for these time trends.…”
Section: Influence Of Randomized Clinical Trial Characteristicsmentioning
confidence: 99%
“…Advanced techniques include the introduction and expression of human genes of interest into test animals so as to provide modeling that is more likely to represent human subjects [ 21 ] . Another increasingly employed technique is the early application in test animals and in human subjects of in vivo labeling of brain target sites of interest with radiolabeled tracer molecules (such as for positron-emission tomography [PET]) as an approach to estimating potency, dosing requirements, and pharmacokinetic measures [ 66,83 ] . Following initial identi fi cation of a promising candidate molecule, the process of drug development usually splits into further pursuit of basic mechanisms of action and [ 39 ] preclinical pharmacological characterization vs. initiation of human and clinical studies, as are summarized in Table 1.7 .…”
Section: Phases Of Drug Developmentmentioning
confidence: 99%
“…These circumstances also can make pooling of data across sites risky, and commercial application of pooled data to all sites (such as for licensing across countries) questionable. Trial complexity and heterogeneity appear to have greater impact on responses during placebo treatments than with active test drugs, possibly as a re fl ection of the phenomenon of regression to the mean or chance outcomes, which are more likely with placebo [ 77,82,83 ] . It is also likely that heterogeneity and compromised control of the conduct of trials have contributed to a noteworthy trend in recent years toward falling drug-placebo contrasts in trials of various types of psychotropic drugs [ 77,83 ] .…”
Section: Effects Of Trial Sizementioning
confidence: 99%
See 1 more Smart Citation